Kepuasan Pengunjung Tentang Fasilitas Pelengkap di Daya Tarik Wisata Taman Bunga Puncak Tonang Kabupaten Pasaman - Angela Tri Kurnia Sari; Hijriyantomi Suyuthie (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
This study aims to determine the review of tourist satisfaction so that tourism utilization goes well. The purpose of this study was to describe tourist satisfaction with complementary facilities in the tourist attraction "Taman Bunga Puncak Tonang, Pasaman Regency". this type of research is descriptive research with quantitative data.”. The variable in this study is an independent variable, namely a review of satisfaction with complementary facilities at a tourist attraction "Taman Bunga Puncak Tonang, Pasaman Regency". This research is a type of quantitative descriptive research, the population of this research is visitors who come to the tourist attraction "Taman Bunga Puncak Tonang, Pasaman Regency". The data collection method used is a structured questionnaire using a Likert scale. Data analysis used descriptive analysis. The results of the study prove that a review of Satisfaction regarding Complementary Facilities in Tourist Attractions "Taman Bunga Puncak Tonang, Pasaman Regency". In total it is quite good with a percentage of 52.58% and an average value of 1.6041, and it is recommended that tourists always pay attention to what is needed by tourists, and protect all facilities available at the "Flower Garden" tourist attraction so that tourists can come back and visit recommend this place to others.